Crisis of Public Trust in Law Enforcement Agencies: TNI, Polri, and Fire Department under the Scrutiny of Law and Political Power - Vidya Sari, Ayu; Rahman Fajar Nusa, Diko (Universitas Sains dan Teknologi Komputer, 2025)
Public trust in state institutions is a fundamental element in maintaining legal legitimacy and political stability. In Indonesia, the dynamics of trust towards the TNI, Polri, and Fire Department reflect the complexity of the relationship between the state and society. This research aims to explore public perception patterns towards these three institutions and understand the factors influencing the fluctuations in trust from a legal and political perspective. This research uses a qualitative approach with an instrumental case study design to explore the dynamics of the public's trust crisis towards law enforcement institutions, namely the military (TNI), the police (Polri), and the fire department (Damkar). Data collection techniques included in-depth interviews, observations, digital documentation, and secondary data analysis from national surveys. The research results show that the Indonesian National Armed Forces (TNI) remain the most trusted institution, especially in rural areas, due to their direct involvement in social activities and development. The fire department consistently earns a high level of trust because it is perceived as neutral, responsive, and non-coercive. Meanwhile, the National Police (Polri) has experienced a drastic decline in public trust, triggered by issues of corruption, police violence, complex bureaucracy, and disparities in law enforcement. This research contributes to strengthening the literature on institutional legitimacy and provides practical implications for formulating policies for reforming law enforcement institutions. These results also affirm that public perception is not only influenced by the normative functions of institutions but also by the intensity of social interactions, digital imagery, and the direct service experiences felt by citizens.